A Review of Advance Care Planning Programs in Long-Term Care Homes: Are They Dementia Friendly? - Abigail Wickson-Griffiths; Sharon Kaasalainen; Jenny Ploeg; Carrie McAiney (Hindawi Limited, 2014)
Background. Persons living with dementia in the long-term care home (LTCH) setting have a number of unique needs, including those related to planning for their futures. It is therefore important to understand the advance care planning (ACP) programs that have been developed and their impact in order for LTCH settings to select a program that best suits residents' needs. Methods. Four electronic databases were searched from 1990 to 2013, for studies that evaluated the impact of advance care planning programs implemented in the LTCH setting. Studies were critically reviewed according to rigour, impact, and the consideration of the values of residents with dementia and their family members according to the Dementia Policy Lens Toolkit. Results and Conclusion. Six ACP programs were included in the review, five of which could be considered more "dementia friendly." The programs indicated a variety of positive impacts in the planning and provision of end-of-life care for residents and their family members, most notably, increased ACP discussion and documentation. In moving forward, it will be important to evaluate the incorporation of residents with dementia's values when designing or implementing ACP interventions in the LTCH settings.